Nanotechnology, an alternative with promising prospects and advantages for the treatment of cardiovascular diseases - Li T (Dove Medical Press, 2018)
Tao Li,* Weitao Liang,* Xijun Xiao, Yongjun Qian Department of Cardiovascular Surgery, West China Hospital, Sichuan University, Chengdu, China *These authors contributed equally to this work Abstract: Cardiovascular diseases (CVDs) are one of the most important causes of mortality and affecting the health status of patients. At the same time, CVDs cause a huge health and economic burden to the whole world. Although a variety of therapeutic drugs and measures have been produced to delay the progress of the disease and improve the quality of life of patients, most of the traditional therapeutic strategies can only cure the symptoms and cannot repair or regenerate the damaged ischemic myocardium. In addition, they may bring some unpleasant side effects. Therefore, it is vital to find and explore new technologies and drugs to solve the shortcomings of conventional treatments. Nanotechnology is a new way of using and manipulating the matter at the molecular scale, whose functional organization is measured in nanometers. Because nanoscale phenomena play an important role in cell signal transduction, enzyme action and cell cycle, nanotechnology is closely related to medical research. The application of nanotechnology in the field of medicine provides an alternative and novel direction for the treatment of CVDs, and shows excellent performance in the field of targeted drug therapy and the development of biomaterials. This review will briefly introduce the latest applications of nanotechnology in the diagnosis and treatment of common CVDs. Keywords: nanotechnology, application, targeted therapy, biomaterials, cardiovascular diseases